AJWA DATES AS A PROTECTIVE AGENT AGAINST LIVER TOXICITY IN RAT - Sheikh, Bassem Y.; Elsaed, Wael M.; Samman, Abdulrahman H.; Sheikh, Bassem Yousef; Bin Ladin, Al-Moalim MA (European Scientific Journal, ESJ, 2014)
Background: Liver toxicity is a worldwide clinical problem caused by a variety of causes. It mostly ends by hepatic fibrosis and or cirrhosis. Materials and methods: Ajwa date extract was prepared from Almadinah AlNawiah ajwa and was given to the animals by gastric gavage at a dose of 1gm/kg/day. CCl4 was dissolved oil at 1: 1 percent and was injected intraperitonealy at a dose of 1.2 ml/ kg of body weight 3 times a week. Fourty adult male rats were divided into five groups. G1 - control group. G2 received CCL4 for 4 weeks. G3 received CCL4 for 12 weeks. G4 received CCL4 and ADE for 4 weeks. G5 received CCL4 and ADE for 12 weeks. Animals were sacrificed and blood samples were collected for SGPT, SGOT and albumin measurements. Liver samples were stained and subjected to image analysis to assess the area percentage of fibrosis. Results: Biochemical analysis showed that ADE treated groups showed a significant lower level of SGPT and SGOT compared to CCL4 treated groups. Light microscopic examination showed that the ADE treated groups showed a decrease in the histological alterations induced by CCL4. The area occupied by collagen fibers was significantly decreased in ADE treated groups. These effects may be due to the rich vitamins and antioxidants in the extract. Conclusion: This study highlights the interest to change toward the use of natural medicinal plants with antioxidant activity for protection against diseases. This may provide a scientific base for the conventional use of ADE as a nutritional protocol of management